Expression of Programmed Cell Death Protein 1 by Tumor-Infiltrating Lymphocytes and Tumor Cells is Associated with Advanced Tumor Stage in Patients with Esophageal Adenocarcinoma - Kollmann, Dagmar; Ignatova, Desislava; Jedamzik, Julia; Chang, Yun-Tsan; Jomrich, Gerd; Paireder, Matthias; Kristo, Ivan; Kazakov, Dmitry; Michal, Michal; Cozzio, Antonio; Hoetzenecker, Wolfram; Schatton, Tobias; et al. (Annals of surgical oncology, 2017)
BACKGROUND: Despite recent advances in the therapy for adenocarcinoma of the esophagogastric junction (AEG), overall prognosis remains poor. Programmed cell death protein 1 (PD1) is a co-inhibitory receptor primarily expressed by T-cells. Tumor cells can escape anticancer immune responses by triggering the PD1 pathway. Moreover, PD1 receptor engagement on cancer cells may trigger tumor-intrinsic growth signals. This study aimed to evaluate the potential clinical relevance of PD1 expression by tumor-infiltrating lymphocytes (TILs) and cancer cells in the AEG. METHODS: Patients with AEG who underwent esophagectomy from 1992 to 2011 were included in the study. Expression of PD1was evaluated by immunohistochemistry and correlated with long-term overall survival (OS), disease-free survival (DFS), and various clinicopathologic parameters. RESULTS: Tumor biospecimens from 168 patients were analyzed. In the analysis, 81% of the patients showed high tumoral frequencies (>5%) of PD1-expressing TILs (TIL-PD1+), and 77% of patient tumors harbored high levels (>5%) of PD1+ cancer cells (cancer-PD1+). Expression of PD1 by TILs and cancer cells correlated significantly (p < 0.05) with patients' tumor stage and lymph node involvement. Compared with the patients who had low tumoral frequencies of PD1+ TILs or cancer cells, the TIL-PD1+ and cancer-PD1+ patients demonstrated significantly reduced DFS in the univariate analysis (5-year DFS: 73.3 vs. 41.9%, log-rank 0.008 and 71.3 vs. 41.6%, p = 0.008, respectively). Additionally, the cancer-PD1+ patients showed significantly decreased OS in the univariate analysis compared with the cancer-PD1- patients (5-year OS: 68.8 vs. 43.5%; p = 0.047). However, these correlations did not reach significance in the multivariate analysis. CONCLUSIONS: The PD1 receptor is expressed by both TILs and cancer cells in AEG. High expression of PD1 is associated with advanced tumor stage and lymph node involvement, but not with survival.
Keywords: senioři; senioři nad 80 let; gastroezofageální junkce; imunohistochemie; antigeny CD279; Lymphocytes, Tumor-Infiltrating; tumor infiltrující lymfocyty; lymfatické metastázy; Middle Aged; mužské pohlaví; Esophagogastric Junction; adenokarcinom; míra přežití; Adult; Programmed Cell Death 1 Receptor; Lymphatic Metastasis; Aged, 80 and over; Neoplasm Staging; Immunohistochemistry; Disease-Free Survival; ženské pohlaví; Humans; Survival Rate; Esophageal Neoplasms; lidé středního věku; staging nádorů; dospělí; Female; Aged; Adenocarcinoma; přežití bez známek nemoci; nádory jícnu; lidé; Male